Portable Tongue-Supported Human Computer Interaction System Design and Implementation - Khan, Masood Mehmood; Quain, R. (IEEE Press, 2014)
Tongue supported human-computer interaction (TSHCI) systems can help critically ill patients interact with both computers and people. These systems can be particularly useful for patients suffering injuries above C7 on their spinal vertebrae. Despite recent successes in their application, several limitations restrict performance of existing TSHCI systems and discourage their use in real life situations. This paper proposes a low-cost, less-intrusive, portable and easy to use design for implementing a TSHCI system. Two applications of the proposed system are reported. Design considerations and performance of the proposed system are also presented.